Mycoplasma pneumoniae-associated mucositis: a novel disorder increasingly encountered in clinical practice. - Öztürk Durmaz, E.; Demircioğlu Duman, D.; Arı, O.; Ayan, İ. and Şahin, S. (European Journal of Pediatric Dermatology, 2020)
Mycoplasma pneumoniae-associated mucositis (MPAM) is a novel and rare disorder, both interesting and confusing for physicians who are unaware of its existence. MPAM is described as an atypical milder variant of Stevens-Johnson syndrome (SJS), triggered by Mycoplasma pneumoniae. Compared to drug-induced SJS or toxic epidermal necrolysis (TEN), MPAM tends to affect children and adolescents, shows a predominantly mucosal pattern (two or more mucosal sites), is associated with pneumonia, runs a milder disease course, displays a favorable prognosis, a low recurrence and mortality rate and uncommon long-term sequelae. Establishing a definitive diagnosis of MPAM may prevent unnecessary hospitalization, offer appropriate management of patients and preclude their stigmatization as victims of drug allergy. Herein we report two children with MPAM, which we believe is increasingly encountered in clinical practice.